2009
DOI: 10.1152/japplphysiol.91128.2008
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary wheel running initially increases adrenal sensitivity to adrenocorticotrophic hormone, which is attenuated with long-term training

Abstract: Campbell JE, Rakhshani N, Fediuc S, Bruni S, Riddell MC. Voluntary wheel running initially increases adrenal sensitivity to adrenocorticotrophic hormone, which is attenuated with long-term training. J Appl Physiol 106: 66 -72, 2009. First published November 13, 2008 doi:10.1152/japplphysiol.91128.2008.-Although exercise is a common and potent activator of the hypothalamic-pituitary adrenal (HPA) axis, the effects of exercise on the acute stress response are not well understood. Here, we investigated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 37 publications
3
29
0
1
Order By: Relevance
“…The HPA-axis response to stressors consists of a sequence of adaptive responses that may have adverse consequences if they are inadequate, or prolonged (Charmandari et al, 2005). Rodents with wheel access typically show a more finely tuned response to stressors, mounting a more robust response than sedentary animals to those with physical components such as forced swim or restraint that would demand sufficient mobilization of energy resources (Campbell et al, 2009;Droste et al, 2007;Droste et al, 2003;Droste et al, 2006), and a more curtailed response to those that are purely psychogenic, such as loud noise or novel cage exposure that would require less energy Droste et al, 2007;Droste et al, 2003). A similar finding is observed in humans in that exercise blunts the HPA-axis response to a single exposure of oral mCPP a 5HT-2C agonist with anxiogenic properties (Broocks et al, 1999;Broocks et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HPA-axis response to stressors consists of a sequence of adaptive responses that may have adverse consequences if they are inadequate, or prolonged (Charmandari et al, 2005). Rodents with wheel access typically show a more finely tuned response to stressors, mounting a more robust response than sedentary animals to those with physical components such as forced swim or restraint that would demand sufficient mobilization of energy resources (Campbell et al, 2009;Droste et al, 2007;Droste et al, 2003;Droste et al, 2006), and a more curtailed response to those that are purely psychogenic, such as loud noise or novel cage exposure that would require less energy Droste et al, 2007;Droste et al, 2003). A similar finding is observed in humans in that exercise blunts the HPA-axis response to a single exposure of oral mCPP a 5HT-2C agonist with anxiogenic properties (Broocks et al, 1999;Broocks et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Wheel running also changes HPA-axis function; for example, wheel running produces elevated CORT at the onset of the diurnal active period in both rats and mice (Adlard and Cotman, 2004;Droste et al, 2003;Fediuc et al, 2006;Stranahan et al, 2006) and is consistently associated with enlarged adrenals Droste et al, 2007;Droste et al, 2003;Droste et al, 2006;Nyhuis et al, 2010;Sasse et al, 2008). The HPA-axis response to both acute (Campbell et al, 2009;Campeau et al, 2010;Droste et al, 2007;Droste et al, 2003;Droste et al, 2006) and repeated Sasse et al, 2008) stress is also altered in wheel-running rodents. Thus, the changes observed in HPA-axis outcomes following wheel running mirror those of chronic stress in some cases (adrenal enlargement, diurnal CORT), and demonstrate stress resistance in others (response to stress).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). It may be that the overall distance run by these animals [ϳ5 km/day compared with 10 -15 km/day for healthy rodents (16,29)] and the variability in animals for these parameters prevent us from observing these expected adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, enhanced glucocorticoid activity in adipose tissue through increased adipose expression of the glucocorticoidactivating enzyme, 11␤-hydroxysteroid dehydrogenase type 1 (11␤HSD1), results in marked central obesity (19), perhaps through increased rates of adipogenesis (18). In contrast to these findings, we recently demonstrated that increased glucocorticoid exposure, through elevated 11␤HSD1 gene expression and activity specifically in the visceral adipose tissue of exercise-trained rodents, was associated with elevations in lipolysis and markedly diminished visceral adiposity (6,7). This discrepancy between glucocorticoid levels and adiposity makes it difficult to draw generalized conclusions regarding the significance of the lipolytic and antilipolytic actions of these hormones.…”
mentioning
confidence: 99%